The geology and alteration/mineralization of the Van Rooi's vley W/Sn deposit, Namaqua metamorphic complex, South Africa - Smithies, Robert Hugh (Rhodes University, Faculty of Science, Department of Geology, 1987)
Scheelite, wolfram Ite and cassIterIte mIneralizat ion is hosted wIthin numerous quartz-tourmaline-feldspar-fluorite veins at Van Rooi's Vley, N.W. Cape Province . MineralizatIon and hydrothermal alteration within, and around, these veins is hIghly complex and reflects the intricate interaction of hydrotherma l activity upon a structurally deformed sequence of ProterozoIc med ium to high-grade gneisses. Four distinct stages of alteration and mineralization occurred, including a l ate 'epithermal stage'. Although the location of mineralization was strongly controlled by st ructure, the concentration of mineralizati on was controlled by physicochemical variables, of which host-rock geochemistry was particularly important . Further W/Sn mineralization occurs on a local scale, some of which is spatia lly related to minor leucogranite dykes. Leucogranite bodies are not uncommon within the region and some are enriched in Wand Sn. By comparing FIB ra tio s,W/Sn ratios, the alteration mineralogy, the ore mineralogy and the Fe-content of tourmaline, the deposits within the Van Rooi's Vley area can be placed into a 'proximal' to 'distal' classification, with respect to a common source of mineralizing hydrothermal fluids. The Van Rooi's Vley deposit, whilst affiliated to greisen-style deposits, represents a ' distal' quartz-vein lode deposit.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Mineralogy -- South Africa; Geology -- South Africa -- Namaqualand